Comparison of salinity effects on grafted and non-grafted eggplants in terms of ion accumulation, MDA content and antioxidative enyzme activities - Talhouni, Manar; Sönmez, Kenan; Sevinç Kiran; Beyaz, Ramazan; Yildiz, Mustafa; Kuşvuran, Şebnem; Şeküre, Şebnem Ellialtıoğlu (Advances in horticultural science, 2019)
Grafting onto resistant/tolerant rootstocks is known to alleviate the negative effects of abiotic stress factors like salinity by enhancing their enzymatic antioxidant defense system and having more efficient nutrient uptake. This study was carried out under greenhouse conditions, different rootstock/scion eggplant combinations were grown under two salinity treatments 1.8-2 dS/m (control) and 6-7 dS/m (stress) with seven eggplant genotypes as rootstocks (commercial and Turkish genotypes). Two genotypes were used as the scion. Leaf MDA and ions (Na+, Cl-, K+ and Ca++) content, antioxidant enzymes activity were evaluated as indicators for plant tolerance level. It was found that the rootstock-grafted plants were more efficient in preventing Na+ ions to be transferred to the plants upper parts and had higher SOD, CAT, and APX activity levels compared to the self- and non-grafted plants which resulted in better tolerance and growth in these plants.